2012
DOI: 10.1007/s00062-011-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Supraclinoid Internal Carotid Artery (ICA) Fenestration in Combination with Duplication of the Middle Cerebral Artery (MCA) Originating from the ICA Fenestration and an Associated Aneurysm

Abstract: Fenestrations and duplications of the cervical and intracranial arteries are rare anatomic variants, reported to be associated with aneurysms or other vascular anomalies. We here present a patient with a supraclinoid ICA fenestration in combination with a duplication of the MCA originating from the ICA fenestration and an associated aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Selected authors noted an association between duplicated MCAs and aneurysms (50,61,62), although very few studies have reported aneurysms at the origin or near the anomalous branch (12,24,29,42,49,57,70). Several authors observed an association between accessory MCAs and aneurysms (30,80,91).…”
Section: Cortical Branchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected authors noted an association between duplicated MCAs and aneurysms (50,61,62), although very few studies have reported aneurysms at the origin or near the anomalous branch (12,24,29,42,49,57,70). Several authors observed an association between accessory MCAs and aneurysms (30,80,91).…”
Section: Cortical Branchesmentioning
confidence: 99%
“…Few studies have, however, reported aneurysms at the origin or near the anomalous branch (14,16,22,41,45,46,51,67,88). Fenestration might predispose patients to aneurysm formation (62) and selected authors have observed an association between fenestration and aneurysms (proximal or distal to the fenestration) (13,44,52,54,62,65,81). trunks included the PfA and precentral artery in 42.1%, the temporopolar artery and ATA in 31.6%, and the PcA and central artery in 31.6% of cases.…”
Section: Cortical Branchesmentioning
confidence: 99%
“…This anomalous vessel is associated with various other intracranial anomalies such accessory MCA, azygos ACA, and moyamoya disease [5] [15]. However, the association of a cerebral aneurysm with this anomaly is very rare, and only 29 treated cases have been reported [1]- [24]. Komiyama et al reported that the DMCAs supplied the cortical territory of the temporopolar and the anterior temporal and/or middle temporal arteries, and they had perforating arteries in three of four cases [27].…”
Section: Discussionmentioning
confidence: 99%
“…In most of them, the DMCAs originate at the base of the aneurysms. In some cases, the aneurysm arises solely from the DMCA rather than the junction of the internal carotid artery and the DMCA [4] [23] [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation